2022
DOI: 10.3390/life12081155
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Pig Semen Using a Quercetin-Supplemented Freezing Extender

Abstract: Reactive oxygen species (ROS) produced during freeze–thaw procedures cause oxidative damage to the sperm, reducing fertility. We aimed to improve the post-thaw quality of pig sperm by quercetin (QRN) supplementation to reduce the cryodamage associated with the freeze–thaw procedure. Four equal aliquots of pooled boar semen were diluted with a freezing extender supplemented with different concentrations of QRN (0, 25, 50, and 100 µM) and then were subjected to cryopreservation in liquid nitrogen. Semen analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In the last decade, a great deal of attention has been focused on the favorable effects of antioxidants on the quality of cryopreserved boar sperm and fertilizing capacity, such as vitamin E [ 5 , 6 ], glutathione [ 7 , 8 , 9 ], l -cysteine [ 10 , 11 ], N -acetyl l -cysteine [ 3 , 12 ] and gamma-oryzanol [ 13 , 14 ]. In recent years, several plant-derived polyphenols such as quercetin (flavonoids) [ 15 ], resveratrol (non-flavonoids) [ 16 ], and curcumin [ 17 ] also revealed their potential antioxidant activities for boar sperm.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, a great deal of attention has been focused on the favorable effects of antioxidants on the quality of cryopreserved boar sperm and fertilizing capacity, such as vitamin E [ 5 , 6 ], glutathione [ 7 , 8 , 9 ], l -cysteine [ 10 , 11 ], N -acetyl l -cysteine [ 3 , 12 ] and gamma-oryzanol [ 13 , 14 ]. In recent years, several plant-derived polyphenols such as quercetin (flavonoids) [ 15 ], resveratrol (non-flavonoids) [ 16 ], and curcumin [ 17 ] also revealed their potential antioxidant activities for boar sperm.…”
Section: Introductionmentioning
confidence: 99%
“…Yeste et al demonstrated the significance of Slo1 in the capacitation and acrosome reactions of boar spermatozoa [24,25]. One of our previous reports showed that quercetin can inhibit human Slo3 current [19], and later, we found quercetin also depolarizes cryopreserved boar sperm [39]. This suggested that Slo3 in boar sperm may be functionally significant in maintaining its membrane potential.…”
Section: Discussionmentioning
confidence: 51%
“…To assess gene expression, the total RNA for the control and myo-inositol-treated groups was prepared using the TRI method [ 34 ] and TRIZOL reagent ® (Molecular Research Center, Inc., Cincinnati, OH, USA) in accordance with the manufacturer’s instructions. Briefly, after thawing at 37 °C for 25 s, spermatozoa were washed twice with DPBS (centrifugation at 160× g for 2 min), and the supernatant was removed.…”
Section: Methodsmentioning
confidence: 99%